2019
DOI: 10.32604/jrm.2019.07592
|View full text |Cite
|
Sign up to set email alerts
|

Compression Behaviors of Parallel Bamboo Strand Lumber Under Static Loading

Abstract: In order to investigate the influence of length and compression directions upon behaviour of parallel bamboo strand lumber (PBSL) specimens, 240 axial compression tests have been performed. With three similar one different typical failure modes, the mechanical performance for PBSL specimens under compression parallel to grain and perpendicular to grain are different as a whole. From the point of the characteristic values, the compression strength parallel to grain is 2.1 times of the compression strength perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…The out-of-plane shear strength decreased markedly as the number of layers increased. 4. The values calculated using the traditional theory was the highest among all four theories.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The out-of-plane shear strength decreased markedly as the number of layers increased. 4. The values calculated using the traditional theory was the highest among all four theories.…”
Section: Discussionmentioning
confidence: 86%
“…RS strength and stiffness in CLT have been identified as key factors that can affect the design and performance of CLT floor systems [1]. To address these concerns, numerous studies have been conducted, including the measurement and prediction of the RS properties of CLT, enhancement of the RS properties of CLT, as well as the evaluation of test set-up configuration and methods [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in order to alleviate the high demand for timber resources in China, the bamboo industry has developed rapidly. With natural bamboo as raw material, a series of new products, such as bamboo-woven plywood, bamboo mat plywood, parallel bamboo strand lumber (PBSL) [5][6][7][8][9], laminated bamboo lumber (LBL) [10][11][12][13][14] and Glubam [15] have been developed by using advanced composite and reconstituted technology and are gradually achieving a high level of industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al [14] compared bending resistance of timber scrimber and bamboo scrimber through experiments, which indicated that the longitudinal flexural modulus of elasticity of bamboo scrimber is better than that of timber scrimber when their densities are larger than 0.7 g/cm 3 and the longitudinal flexural strength of bamboo scrimber is better than that of timber scrimber when their densities are larger than 0.8 g/cm 3 . Many scholars have studied different aspects of bamboo scrimber, such as mechanical properties [15][16][17], flame retardant properties [18,19] and material modification [20,21].…”
Section: Introductionmentioning
confidence: 99%